Admissible Classes of Seven-Parameter Mittag-Leffler Operatorwith Third-Order Differential Subordination Properties - Rasheed, Maryam K.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2024)
The main purpose of this paper, is to characterize new admissible classes of linear operator in terms of seven-parameter Mittag-Leffler function, and discuss sufficient conditions in order to achieve certain third-order differential subordination and superordination results. In addition, some linked sandwich theorems involving these classes had been obtained.